Aplikasi Teknologi Tepat Guna untuk Meningkatkan Mutu Madu Klanceng dan Propolis - Gusti Fauza; Siswanti Siswanti; Setyaningrum Ariviani; Dwi Ishartani; Windi Atmaka; Dimas Rahadian Aji Muhammad; Sultan Rafli; Habib Achmad Prasetyo (PRIMA: Journal of Community Empowering and Services, 2026)
Application of Frozen Storage Technology to Maintain the Quality of Klanceng Honey and Propolis. Klanceng honey and propolis are high-value products from stingless bee cultivation, yet their quality is often constrained by high moisture content, poor harvest hygiene, and limited storage technology. The Small and Medium Enterprise (SME) “Madu Klanceng Ceper” faces challenges including a short shelf life (two months), substandard packaging, and limited production capacity. This community service program aimed to enhance product quality and shelf life through improved production tools, frozen storage technology, and packaging development. Activities included training on food dehydrator use to lower honey moisture, provision of protective equipment and honey extractors to improve hygiene and efficiency, supply of freezer boxes to delay fermentation and expand storage capacity, and dissemination of packaging and labeling standards. The program resulted in reduced honey moisture (0,97%) compared to the previous product. The observation of product shelf life showed that up to the sixth month there were no signs of deterioration, and no gas ormation was observed in the honey as a result of fermentation. In addition, the harvesting time decreased from three hours to one hour, and the packaging became safer, more attractive, and more informative.